Mixed Use Green Park Subang Dengan Pendekatan Konsep Futuristic Green Building - Purnama Sakhrial Pradini; Vian Nugraha (Prosiding Sains dan Teknologi, 2022)
Environmental problems, especially global warming, have become a topic of problems that have emerged recently. In the world of architecture, the phenomenon of sick building syndrome appears, namely health problems and discomfort due to air quality and air pollution in occupied buildings that affect occupant productivity, poor air ventilation, lack of natural lighting, and glass material as a building wrapper that causes a greenhouse effect. Apart from global warming, the creation or innovation of renewable energy is also the background for the emergence of the concept of Green Architecture. Until finally emerged the concept of Green Building. Energy Saving Buildings, also known as Green Buildings, continue to be promoted as one of the anticipatory steps towards global climate change. Architectural indications are referred to as 'Green' if it is associated with architectural practices, including the use of renewable resources (renewable sources), passive-active solar photovoltaic (solar cells for power generation), techniques for using plants for roofs, rain-fed gardens, using gravel. compacted for the pavement area, andso on. Keyword: Mixed Use, Green Park Subang, Futuristic, Green Building